Controlling Pests Sorghum using Integrated Pest Management as an Alternative Food in Northern Sumatera, Indonesia - Siregar, Ameilia Zuliyanti (Jurnal Ilmu-Ilmu Pertanian, 2025)
The purpose of this study was to determine the composition and comparison of species richness, diversity, and insect dominance in the phases of sorghum. This research was conducted from August to October 2021 in Lalang Village, Tebing Tinggi, at the location of a Sorghum monoculture (Sorghum bicolor). This study uses the purposive random sampling method, where insects are collected using 4 traps (yellow sticky trap, sweep net, pitfall trap, and light trap) installed according to standard regulations. The results showed that the insects identified in Sorghum consisted of 8 orders, 14 families (Chrysomelidae, Muscidae, Alydidae, Pentatomidae, Cicadellidae, Aphididae, Apidae, Sphecidae, Formicidae, Noctuidae, Acrididae, Grylidae, Aeshnidae, Libellulidae) with a total of 6499 individuals. There are 27 genera detected with 5 insect functional statuses, as pollinators (13 species), predators (5 species), herbivores (5 species), parasitoids (1 species), and decomposers (3 species). Knowing the functional status of insects in sorghum cultivation, it is predicted to control pests in an integrated manner in the future. The plant extracts, variances of pheromones, and the minimal use of chemicals in the integrated pest control system can increase the productivity of sorghum.